Telangiectasia-ectodermal dysplasia-brachydactyly-cardiac anomaly syndrome is caused by de novo mutations in protein kinase D1. Issue 6 (17th August 2020) - Alter, Svenja; Zimmer, Andreas David; Park, Misun; Gong, Jianli; Caliebe, Almuth; Fölster-Holst, Regina; Torrelo, Antonio; Colmenero, Isabel; Steinberg, Susan F; Fischer, Judith
Abstract : Background: We describe two unrelated patients who display similar clinical features including telangiectasia, ectodermal dysplasia, brachydactyly and congenital heart disease. Methods: We performed trio whole exome sequencing and functional analysis using in vitro kinase assays with recombinant proteins. Results: We identified two different de novo mutations in protein kinase D1 ( PRKD1, NM_002742.2): c.1774G>C, p.(Gly592Arg) and c.1808G>A, p.(Arg603His), one in each patient. PRKD1 ( PKD1, HGNC:9407) encodes a kinase that is a member of the protein kinase D (PKD) family of serine/threonine protein kinases involved in diverse cellular processes such as cell differentiation and proliferation and cell migration as well as vesicle transport and angiogenesis. Functional analysis using in vitro kinase assays with recombinant proteins showed that the mutation c.1808G>A, p.(Arg603His) represents a gain-of-function mutation encoding an enzyme with a constitutive, lipid-independent catalytic activity. The mutation c.1774G>C, p.(Gly592Arg) in contrast shows a defect in substrate phosphorylation representing a loss-of-function mutation. Conclusion: The present cases represent a syndrome, which associates symptoms from several different organ systems: skin, teeth, bones and heart, caused by heterozygous de novo mutations in PRKD1 and expands the clinical spectrum of PRKD1 mutations, which have hitherto been linked to syndromic congenital heart disease and limb abnormalities.